The Association Between Brain Volumes and Posttraumatic Stress Disorder in Intensive Care Unit Survivors: A Preliminary Study - Stepanovic, Kristina; Rogers, Baxter; Kiehl, Amy L.; Ely, E. Wesley; Jackson, James; Wilson, Jo Ellen; , for the VISIONS Investigators and VISualizing Icu SurvivOrs Neuroradiological Sequelae Cohort Study (Frontiers in Neuroscience, 2020)
Introduction: Millions of Americans are admitted to the intensive care unit per year. Many survivors of the intensive care unit (ICU) will experience posttraumatic stress disorder (PTSD); although volumetric hippocampal and amygdala studies have been conducted in other trauma survivors (ie veterans), the association between PTSD symptoms and hippocampal and amygdala volumes in ICU survivors has not been described. We hypothesize that the severity of posttraumatic stress symptoms in ICU survivors is associated with lower volumes of both the hippocampus and amygdala at 3 and 12 months. Methods: Secondary analysis of the VISIONS study, a prospective sub-study of the BRAIN-ICU cohort, which included survivors of critical illness. The PTSD Checklist Specific (PCL-S) was used at 3 and 12 months to evaluate the ICU as a traumatic experience. A Philips Achieva 3T MRI scanner was used to scan patients at both discharge and 3 months. To compare median brain volumes at discharge and 3 months for those with and without PTSD symptomatology, we used a Kruskal-Wallis (KW) test. Results: At 3 month follow up, 3 patients had PTSD symptomatology and N=1 at 12 month follow up. There was no difference between median brain volumes (hippocampus or amygdala) between individuals with PTSD symptomatology at either 3 or 12 months (p-values >0.05). Discussion: Although our study did not reveal significant differences in brain volumes between PTSD patients and non-PTSD patients, sample size was a major limitation and larger scale studies should be undertaken to elucidate possible neurobiological markers of PTSD in ICU survivors.